Transformasi Hukum Waris Adat dalam Perspektif Syariat Islam Dan Kearifan Lokal di Indonesia: Transformation of Customary Inheritance Law from the Perspective of Islamic Sharia and Local Wisdom - Lukman Ansar; Tarmizi Tarmizi; Sabar Podu (ISTIDLAL, 2026)
This study aims to analyze the transformation of customary inheritance law from the perspective of Islamic sharia and local wisdom in Indonesia. As a living legal system within society, customary inheritance law has evolved in tandem with social and cultural changes and the influence of religious values. This study employs a normative legal research method, utilizing legislative, conceptual, and historical approaches. Research data was obtained through a literature review of various primary, secondary, and tertiary legal materials related to customary inheritance law and Islamic inheritance law. The research findings indicate that the transformation of customary inheritance law occurs through a process of adaptation between local traditions and the principles of Islamic sharia. These changes are evident in the development of a more open inheritance system, the recognition of women’s rights as heirs, and the implementation of family deliberation that prioritizes the common good and social harmony. This study also found that customary law and Islamic law are not always in a conflictual relationship; rather, they can complement each other in forming an inheritance system that is contextual and responsive to the development of modern society. Therefore, harmonization between customary law and Islamic Sharia is crucial in realizing an inheritance system that is just, humane, and continues to respect the cultural diversity of Indonesian society